Hypertension is a risk factor for adverse outcomes in patients with coronavirus disease 2019: a cohort study. (2nd October 2020) - Xiong, Tian-Yuan; Huang, Fang-Yang; Liu, Qi; Peng, Yong; Xu, Yuan-Ning; Wei, Jia-Fu; Li, Nian; Bai, Bei; Li, Jun-Hua; Prendergast, Bernard; Li, Wei-Min; Chen, Mao
Abstract: Background: Comorbidities are commonly seen in patients with coronavirus disease 2019 (COVID-19), but the clinical implication is not yet well-delineated. We aim to characterize the prevalence and clinical implications of comorbidities in patients with COVID-19. Methods: This is a retrospective multi-centre study involving patients admitted between January 16th and March 10th 2020. The composite endpoint was defined as the presence of at least one of the following, intensive care unit (ICU) admission, or the need for mechanical ventilation, or death. Results: A total of 472 consecutive cases admitted to 51 certified COVID-19 tertiary care hospitals were enrolled (median age was 43 [32–53.5] years and 53.0% were male). There were 101 (21.4%) patients presented with comorbidities, including hypertension (15.0%), diabetes mellitus (7.8%), coronary artery disease (2.6%), chronic obstructive pulmonary disease (1.3%) and cerebrovascular disease (1.9%). The composite endpoint occurred in 65 (13.8%) patients. Multivariate stepwise logistic regression analysis indicated that older age (odds ratio [OR] 1.39, 95% confidence interval (CI) 1.05–1.85, per 10-year increment), antecedent hypertension (OR 2.82, 95% CI 1.09–7.29), neutrophil counts (OR 1.33, 95% CI 1.14–1.56) and lactate dehydrogenase level (OR 1.01, 95% CI 1.00–1.01) were independently associated with the presence of composite endpoint. Hypertensive patients, compared with controls, had a greater chance of experiencing the composite endpoint ( p  < .001) and each individual endpoint, i.e. ICU admission ( p  < .001), mechanical ventilation ( p  < .001) and death ( p  = .012). In the stepwise regression analysis of anti-hypertensive medications, none of the therapy predicted the composite endpoint. Conclusions: Hypertension is a common comorbidity in patients with COVID-19 and associated with adverse outcomes. KEY MESSAGES: Hypertension was identified as the comorbidity associated with the prognosis of COVID-19 in this retrospective cohort. Patients with hypertension could experience an increased risk of the composite endpoint. Anti-hypertensive therapy did not affect patient outcomes.